2010
DOI: 10.1063/1.3445780
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of geometric shape and periodicity to resonant terahertz transmission

Abstract: We report the terahertz (THz) transmission characteristics of subwavelength slit arrays with a variety of structures ranging from periodic to random. THz electromagnetic wave transmission experiments clarify the relative contributions of the periodicity and the geometric shape effects to transmission enhancement. In the spectral region slightly below the first Rayleigh minimum, strong transmission enhancement is achieved through the contributions of both effects. In the long-wavelength region, however, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…More recently, the rigorous coupled-wave analysis (RCWA), an elegantly simple model based on modal expansion of the fields, has been used to study single apertures and arrays [13]. Apart from the designation of periodicity, studies have indicated that the transmission through arrays of subwavelength apertures strongly depends on aperture shape [14][15][16][17]. Although a comprehensive study has been made on researching the transmission behavior through metal aperture arrays, there is not yet a consensus on the mechanism underlying the physical phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the rigorous coupled-wave analysis (RCWA), an elegantly simple model based on modal expansion of the fields, has been used to study single apertures and arrays [13]. Apart from the designation of periodicity, studies have indicated that the transmission through arrays of subwavelength apertures strongly depends on aperture shape [14][15][16][17]. Although a comprehensive study has been made on researching the transmission behavior through metal aperture arrays, there is not yet a consensus on the mechanism underlying the physical phenomena.…”
Section: Introductionmentioning
confidence: 99%